Traditional Knowledge, Agave Inaequidens (Koch) Conservation, and the Charro Lariat Artisans of San Miguel Cuyutlán, Mexico - Valenzuela-Zapata, Ana G.; Lopez-Muraira, Irma; Gaytán, Marie Sarita (Ethnobiology Letters, 2011)
The Mexican sport of charrería, or Mexican rodeo, developed in post-conquest Mexico as a way of preserving and celebrating traditional cowboy riding and livestock handling skills. Today, charrería is considered the national sport of Mexico and the charro (cowboy) is also a celebrated icon of Mexicanness. Special handcrafted ropes used in charrería, known as sogas finas, or charro lariats, are made from the fibers of the Agave inaequidens. The manufacture of charro ropes is an artisinal practice that requires both cultural and botanical knowlege. In the last ten years, there has been a significant decline in the A. inaequidens population in the Cerro Viejo mountain range of the central-western Mexican state of Jalisco, putting the financial wellbeing of local lariat artisans at risk. Drawing on fieldwork and laboratory analysis conducted from 2002 through 2010, we discuss the socio-cultural significance of charro lariats, detail the harvesting of A. inaequidens in relation to lariat craftsmanship, document the physical characteristics of the A. inaequidens from this region, and describe the relationship between traditional knowledge and the local economy. The goal of this research is two-fold: 1) to stimulate feedback between producers and consumers in an attempt to leverage the existing business cluster based on traditional knowledge and 2) to initiate dialogue concerning conservation, domestication, and sustainable management of the wild A. inadequidens population.